Use of prisms in ophthalmology: a review. Part 2. Use of prisms in heterophoria, nystagmus, and visual nervous system disorders - Use of prisms in ophthalmology: a review. Part 2. Use of prisms in heterophoria, nystagmus, and visual nervous system disorders (Ukrainian Society of Ophthalmologists, 2022)
Prism correction can be helpful not only for patients with strabismus, but also for those with other eye conditions. In heterophoria, especially in the presence of asthenopic complaints, prisms can be used for compensation for latent strabismus and development of fusional reserves. Prisms can reduce an abnormal head posture and thus normalize the posture of a child in jerk nystagmus. Base-out prisms are prescribed to induce divergence and stimulate fusional convergence for decreasing the amplitude of nystagmus and thus improving visual acuity in patients whose nystagmus is suppressed by viewing a near target. In patients whose nystagmus is worse during near viewing, base-in prisms may help which induce divergence. Prisms can be helpful for eliminating diplopia in thyroid eye disease and are used for assessing the Accommodative Convergence to Accommodation (AC/A) ratio. They can be also helpful to shift the image from the affected fovea to the preferred retinal locus in patients with absolute central scotoma and eccentric gaze fixation and to expand visual fields in patients with hemianopia and retinitis pigmentosa. Ophthalmologists should bear in mind that the above conditions can be treated with prisms, and apply prism correction widely in their practice.